Microbial Inventory of Deeply Buried Oceanic Crust from a Young Ridge Flank - Jørgensen, Steffen L.; Zhao, Rui (Frontiers in Microbiology, 2016)
The deep marine biosphere has over the past decades been exposed as an immense habitat for microorganisms with wide-reaching implications for our understanding of life on Earth. Recent advances in knowledge concerning this biosphere have been achieved mainly through extensive microbial and geochemical studies of deep marine sediments. However, the oceanic crust buried beneath the sediments, is still largely unexplored with respect to even the most fundamental questions related to microbial life. Here we present quantitative and qualitative data related to the microbial inventory from 33 deeply buried basaltic rocks collected at two different locations, penetrating 300 vertical meters into the upper oceanic crust on the west flank of the Mid-Atlantic spreading ridge. We use quantitative PCR and sequencing of 16S rRNA gene amplicons to estimate cell abundances and to profile the community structure. Our data suggest that the number of cells is relatively stable at ~104 per gram of rock irrespectively of sampling site and depth. Further, we show that Proteobacteria, especially Gammaproteobacteria dominate the microbial assemblage across all investigated samples, with Archaea, in general, represented by less than 1% of the community. In addition, we show that the communities within the crust are distinct from the overlying sediment. However, many of their respective microbial inhabitants are shared between the two biomes, but with markedly different relative distributions. Our study provides fundamental information with respect to abundance, distribution and identity of microorganisms in the upper oceanic crust.